Gender differences in healthcare management of depression: aspects of sick leave and treatment with psychoactive drugs in a Swedish setting. (3rd October 2019) - Lytsy, Per; Hallqvist, Johan; Alexanderson, Kristina; Åhs, Annika
Abstract: Purpose: To investigate whether women and men diagnosed with depressive disorder were managed equally in terms of being sick-leave certified and being prescribed psychoactive drugs. Materials and methods: Data from all patients diagnosed with depression during 2010–2015 in Uppsala county, Sweden ( n  = 19 448) were used to investigate associations between gender and issued sick-leave certificate, prescriptions of anti-depressants, anxiolytics, hypnotics and sedatives, and cognitive behavioral psychotherapy referrals, at different time points up till 180 days after diagnosis. Results: At diagnosis date, 50.1% were prescribed antidepressants; 14.2% anxiolytics; 13.3% hypnotics or sedatives. Corresponding proportion regarding issue of sick-leave certificate among working aged (18–64 years) was 16.6%. Men had higher odds than women of being prescribed antidepressants (OR 1.16; 95% CI 1.09–1.24); anxiolytics (1.10; 95% CI 1.02–1.21), hypnotics and sedatives (OR 1.09; 95% CI 1.00–1.19) and lower odds (among those aged 18–64 years) of being sick-leave certified (OR 0.90; 95% CI 0.82-0.98) in adjusted regression models. There were subtle changes in ORs for outcomes at 3- and 6-month follow-up periods. Conclusions: Men had somewhat higher odds of being prescribed psychoactive drugs and slightly lower odds of being sick-leave certified as compared to women at date when diagnosed with depression. The absolute differences were, however, small and the overall conclusion is that women and men with current diagnosed depressive episode/recurrent depressive disorder are generally managed likewise regarding sick leave and psychoactive treatment.